The impact of increasing urban surface albedo on outdoor air and surface temperatures during summer in newly developed areas - Donia Elgendy; Osama Tolba; Tarek Kamel (Scientific Reports)
Abstract This study investigates the influence of increasing road surface albedo on outdoor air and surface temperatures in residential areas, taking into account constraints on broader environmental modifications. Urban albedo, which is determined by spatial geometry and material reflectance, influences the amount of solar radiation bouncing back into the atmosphere. Field measurements were conducted on-site to document Air Temperature (Ta), Wind Speed (WS), Relative Humidity (RH), Mean Radiant Temperature (MRT) providing the basis for validating simulation models. The urban geometry was reconstructed from real site data and simulated using a hybrid modeling approach, combining Ladybug with Grasshopper for Surface Temperature (Ts), MRT, and Universal Thermal Climate Index simulations, and ENVI-met for Ta, RH, and WS simulations. ENVI-met outputs were integrated into Grasshopper to achieve high-accuracy environmental modeling. Results demonstrate that increasing pavement albedo from 0.12 to 0.50 reduced Ts by up to 12.94 °C at peak solar hours and lowered Ta by a maximum of 1.96 °C during the day. The research addresses a critical gap by focusing solely on altering material reflectivity without changing urban morphology or adding any canopies either structured or vegetation. The findings confirm that enhancing surface albedo is an effective method to reduce daytime heat trapping & accumulation, and shortwave radiation absorption which mitigate the Urban Heat Island phenomenon.